A facile one pot synthetic approach for C3N4–ZnS composite interfaces as heterojunctions for sunlight-induced multifunctional photocatalytic applications. Issue 22 (12th February 2016) - Suyana, P.; K. R., Sneha; Nair, Balagopal N.; Karunakaran, Venugopal; Mohamed, A. Peer; Warrier, K. G. K.; Hareesh, U. S.
Abstract : Herein, we report a facile one pot synthetic protocol for the creation of C3 N4 –ZnS composite interfaces by the co-pyrolysis of a precursor mix containing zinc nitrate, melamine, and thiourea at 550 °C in air. Abstract : Herein, we report a facile one pot synthetic protocol for the creation of C3 N4 –ZnS composite interfaces by the co-pyrolysis of a precursor mix containing zinc nitrate, melamine, and thiourea at 550 °C in air. The organic–inorganic semiconductor heterojunctions thus formed displayed increased absorbance in the longer wavelength region and facilitated broad absorption of visible light compared to pure ZnS, C3 N4 and conventionally synthesized hybrid samples. The decreased emission intensity, increased photocurrent generation and decreased fluorescence lifetime revealed reduced exciton recombinations in the co-pyrolysed sample containing C3 N4 –ZnS heterostructures. The samples displayed sunlight driven photocatalytic reduction of nitrophenol as well as hydrogen generation (4 mmol g −1 h −1 ) by water splitting.